(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
Ibn Sina (Avicenna) was a renowned Persian scholar and physician of the medieval period whose works greatly influenced the development of medicine worldwide. His most famous work, "The Canon of Medicine" (Al-Qanun fi al-Tibb), served as a principal medical reference for many centuries. This book significantly impacted the advancement of both traditional and scientific medicine.